SAT0221 Efficacy and Safety of PF-04171327, a Novel Dissociated Agonist of the Glucocorticoid Receptor (DAGR): Results of a Phase 2, Randomized, Double-Blind Study. (9th June 2015) - Buttgereit, F.; Strand, V.; Lee, E.B.; McCabe, D.; Kolluri, S.; Tammara, B.; Rojo, R.; Hey-Hadavi, J.
Abstract : Background: Glucocorticoids (GC) are widely used to treat rheumatic and other diseases, but adverse effects limit their full potential. Improvement of their benefit-risk ratio represents both a current need and an ongoing challenge. One promising option includes dissociated agonists of the glucocorticoid receptor (DAGR) with the efficacy of higher dose GCs and the safety profile of lower dose GCs. Objectives: PF-04171327, a DAGR, represents a first-in-class compound under investigation for the treatment of rheumatoid arthritis. The aim was to test the above hypothesis that this novel drug preferentially exerts transrepression mediated effects thereby inducing potent therapeutic activity with reduced adverse effects. Methods: 323 adult patients with active RA (≥6 TJC and 6 SJC plus CRP ≥0.7 mg/dL) receiving MTX were randomized to receive DAGR 1, 5, 10 or 15 mg, prednisone (pred) 5 or 10 mg, or placebo (PBO) QD for 8 weeks followed by a 4-week taper period, and an ACTH stimulation test at Week 13. Use of GCs within 6 weeks of screening was prohibited. Efficacy analyses included characterization of dose-response at Week 8 for primary and secondary efficacy endpoints: ACR20 and DAS28-4(CRP). Effects on bone formation (P1NP, osteocalcin) and resorption (uNTX/uCr, sCTX) biomarkers, fasting plasma glucose and HbA1c were assessed for safety in addition to AEs and laboratory tests. Results: Based on ACR20 responses, DAGR 10 and 15 mg QD were superior (by 20% with 80% confidence) to PBO; and DAGR 15 mg QD was non-inferior (by a margin of 5% with 80% confidence) to pred 10 mg QD. DAS28-4(CRP) results were consistent with ACR20 responses. 1, 5, 10 and 15 mg QD doses of DAGR were comparable to pred 5mg QD in bone formation; with small decreases in HbA1c in these predominantly non-diabetes patients. No clear trends or dose-response were seen in bone resorption markers. Prompt HPA axis recovery was evident at Week 13 in all patients. All DAGR doses were well-tolerated (comparable to PBO and pred doses), with no safety signal identified. Conclusions: The aggregate efficacy analysis demonstrated that both DAGR 10 and 15 mg QD have efficacy superior to PBO and comparable to pred 10 mg QD, with bone and glucose effects comparable to pred 5 mg QD. All DAGR doses were safe and well-tolerated. This 8-week RCT provides first clinical evidence to demonstrate that PF-04171327 increases the transrepression/transactivation ratio, thereby improving the GC benefit-risk ratio compared with prednisone in RA patients. Disclosure of Interest: F. Buttgereit Grant/research support from: Pfizer, V. Strand Consultant for: Pfizer, E. Lee Grant/research support from: Pfizer, D. McCabe Employee of: Pfizer, S. Kolluri Employee of: Pfizer, B. Tammara Employee of: Pfizer, R. Rojo Employee of: Pfizer, J. Hey-Hadavi Employee of: Pfizer